DNA from Buccal Swabs Suitable for High-Throughput SNP Multiplex Analysis - McMichael, Gai L. (Association of Biomolecular Resource Facilities, 2009)
We sought a convenient and reliable method for collection of genetic material that is inexpensive and noninvasive and suitable for self-collection and mailing and a compatible, commercial DNA extraction protocol to meet quantitative and qualitative requirements for high-throughput single nucleotide polymorphism (SNP) multiplex analysis on an automated platform. Buccal swabs were collected from 34 individuals as part of a pilot study to test commercially available buccal swabs and DNA extraction kits. DNA was quantified on a spectrofluorometer with Picogreen dsDNA prior to testing the DNA integrity with predesigned SNP multiplex assays. Based on the pilot study results, the Catch-All swabs and Isohelix buccal DNA isolation kit were selected for our high-throughput application and extended to a further 1140 samples as part of a large cohort study. The average DNA yield in the pilot study (n=34) was 1.94 μg ± 0.54 with a 94% genotyping pass rate. For the high-throughput application (n=1140), the average DNA yield was 2.44 μg ± 1.74 with a ≥93% genotyping pass rate. The Catch-All buccal swabs are a convenient and cost-effective alternative to blood sampling. Combined with the Isohelix buccal DNA isolation kit, they provided DNA of sufficient quantity and quality for high-throughput SNP multiplex analysis.